The Evergreen Challenges of Healing: an Evaluation of Urban Green Space in Harambee - (:unkn) unknown (My University, 2022)
Urban green space initiatives have emerged in low- and middle-income cities as a solution to disinvestment, the production of more positive public health metrics, and a tool of community engagement. While the production of urban greening provides ample room for applause, The City of Milwaukee’s Healing Spaces Initiative model regarding the ongoing construction of green space and the implementation of maintenance creates challenges that perpetuate racist capitalistic notions of the neoliberal project. This paper presents reports from participant observation, document analysis, and 17 qualitative interviews with representatives of the City of Milwaukee, community partners, garden leaders, and residents. The data suggest that the needs of the residents are beyond what the City of Milwaukee can provide. Therefore, they use collaborative community partnerships and outside funding to piece together the social support to serve residents while maintaining control over decision-making, even when outside vendors do the work. The result of this is disjointed service and confused residents. Through the tenacity of individual actors and residents, Healing Spaces Initiative remains a success despite various challenges. Resolving these issues by engaging in a new strategic direction for neighborhood beautification is essential to preserving the right to green space.
Keywords: Community Development; Local Governance; Local Government; Neoliberalism; Urban Greening; Urban Studies